Subextension and approximation of $m$-subharmonic functions with given boundary values - Amal, Hichame; El Gasmi, Ayoub (Ukrains’kyi Matematychnyi Zhurnal, 2025)
UDC 517.5We establish a result on subextension of $m$-subharmonic functions in the class $\mathcal{F}_m(Ω,f)$ without changing the Hessian measures. As application, we approximate an $m$-subharmonic function with given boundary value by an increasing sequence of $m$-subharmonic functions defined in larger domains.